Perovskite Solar Cells: Stable Formamidinium‐Based Perovskite Solar Cells via In Situ Grain Encapsulation (Adv. Energy Mater. 22/2018). Issue 22 (6th August 2018) - Liu, Tanghao; Zhou, Yuanyuan; Li, Zhen; Zhang, Lin; Ju, Ming‐Gang; Luo, Deying; Yang, Ye; Yang, Mengjin; Kim, Dong Hoe; Yang, Wenqiang; Padture, Nitin P.; Beard, Matthew C.; et al.
Abstract : In article1800232, Yuanyuan Zhou, Kai Zhu, Rui Zhu, and co‐workers demonstrate in situ encapsulating perovskite grains with silica. Silica can protect perovskite grains from the air and reduce the charge recombination on the surface of perovskite films. Based on the silica encapsulated perovskite grains, perovskite solar cells achieved improved efficiency and stability.